Digital fanfic in negotiation: LiveJournal, Archive of Our Own, and the affordances of read–write platforms. (August 2020) - Fathallah, Judith
Fanfic is the unauthorized rewriting or adaptation of popular media narratives, utilizing corporately owned characters, settings and storylines to tell an individual writer's own story. It is often abbreviated to fanfic or even fic and exists in a thoroughly grey legal area between copyright infringement and fair use. Although there were a few cases of cease-and-desist letters sent to fan writers in the 20th century, media corporations now understand it is useless to attempt to prosecute fanfic writers – for one thing, there are simply too many of us and for another it would be terrible publicity. Although modern fanfic can be reliably dated to the 1960s, it is now primarily an online practice and the fastest growing form of writing in the world. This article uses participant observation and online ethnography to explore how fanfic archives utilize digital affordances. Following Murray, I will argue that a robust understanding of digital read–write platforms needs to account for the social and legal context of digital fiction as well as its technological affordances. While the online platform LiveJournal in some ways channels user creativity towards a more self-evidentially 'digital' text than its successor in the Archive of Our Own (AO3), the Archive encourages greater reader interactivity at the level of archive and sorting. I will demonstrate that in some ways, the AO3 recoups some of the cultural capital and use value of print. I argue that a true appreciation of digital fiction is less about projecting fiction as becoming more and more 'digital' along a linear trajectory than application of a nuanced sociotechnological perspective that addresses the aims, ideology and provision of particular platforms in practice.